Unravelling the relationship between language anxiety and foreign language speech fluency in a monologue production - Szyszka, Magdalena; Peltonen, Pauliina; Lintunen, Pekka (Routledge, 2025)
This study investigated the interplay between language anxiety of advanced foreign language learners and their speech fluency measured with temporal indices. Language anxiety levels of 59 university level students of English were identified with the Input, Processing and Output Anxiety Scale (the IPOAS; MacIntyre & Gardner, 1994) and the Post-Session Survey on Anxiety. The former informed about the levels of anxiety experienced at three stages of linguistic processing, hence, input anxiety, internal processing anxiety, and output anxiety. The latter was applied to identify language anxiety levels exhibited during a monologue production, reported as task-specific language anxiety. Speech samples from the performance were analyzed for fluency breakdown (the number of filled and silent pauses), speed of speech (articulation rate), and composite measures (speech rate). The findings revealed that the advanced foreign language learners with higher levels of internal processing anxiety and output anxiety used filled pauses more frequently. Furthermore, the levels of output anxiety and task-specific language anxiety were inversely related to speech and articulation rate. The study also showed statistically significant differences in the production of filled pauses and speech rate between advanced foreign language learners with low and high levels of language anxiety as measured by the IPOAS.